BUMNAG Karya Bersama Strategy in Developing Savings and Loan Business Units in Lubuk Bunta Village Silaut Subdistrict South Pesisir Regency - Waza Karia Akbar; Vera Febrianti; Jaenam Jaenam; Erita Erita; Zidni Ilman Nafian (LPPM Universitas PGRI Sumatera Barat, 2025)
This study is motivated by the popularity of BUMNag ‘karya bersama’ among the community as a source of business capital, resulting in BUMNag ‘karya bersama’ employing various strategies to attract customers to borrow from them. The purpose of this study is to describe the strategies of BUMNag Karya Bersama in developing savings and loan business units in Nagari Lubuk Bunta, Silaut District, Pesisir Selatan Regency.This research uses Chandler's (1962) theory of corporate strategy, which discusses company scale, scope and limitations, as well as internal structure and design. The approach used in this research is qualitative with a descriptive research type with 15 informants. Data collection techniques were carried out through observation, interviews, and document studies. The unit of analysis in this study is a group. The results of this study show that the BUMNag ‘karya bersama’ strategy in developing savings and loan business units in Nagari Lubuk Bunta, Silaut District, Pesisir Selatan Regency is: 1) Promoting BUMNag in community activities. 2) Giving rewards to customers who pay on time during the loan period. 3) There are no collateral requirements for business capital loans for customers. 4) Lower interest rates. 5) A loan process that is unconditional and fast. 6) Establishing good relationships with customers.